Aberrant Amplitude of Low-Frequency Fluctuations in Different Frequency Bands in Patients With Parkinson’s Disease - Wang, Zhaoxiu; Liu, Yanjun; Ruan, Xiuhang; Li, Yuting; Li, E.; Zhang, Guoqin; Li, Mengyan; Wei, Xinhua (Frontiers in Aging Neuroscience, 2020)
Abstract Previous studies reported abnormal spontaneous neural activity in Parkinson’s disease (PD) patients using resting-state functional magnetic resonance imaging (R-fMRI). However, the frequency-dependent neural activity in PD is largely unknown. Here, thirty-five PD patients and thirty-five age- and education-matched healthy controls (HC) underwent R-fMRI scanning to investigate abnormal spontaneous neural activity of PD using the amplitude of low-frequency fluctuation (ALFF) approach within the conventional band (typical band: 0.01-0.08 Hz) and specific frequency bands (slow-5: 0.010-0.027 Hz and slow-4: 0.027-0.073 Hz). Compared with HC, PD patients exhibited increased ALFF in the parieto-temporo-occipital regions, such as the bilateral inferior temporal gyrus/fusiform gyrus (ITG/FG) and left angular gyrus/posterior middle temporal gyrus (AG/pMTG), and displayed decreased ALFF in the left cerebellum, right precuneus and left postcentral gyrus/supramarginal gyrus (PostC/SMG) in the typical band. Furthermore, PD patients showed greater increased ALFF in the left caudate/putamen, left anterior cingulate cortex/medial superior frontal gyrus (ACC/mSFG), left middle cingulate cortex (MCC), right ITG, and left hippocampus, along with greater decreased ALFF in the left pallidum in the slow-5 band, whereas greater increased ALFF in the left ITG/FG/Hippocampus accompanied by greater decreased ALFF in the precentral/postcentral gyrus were found in the slow-4 band (uncorrected). Additionally, the left caudate/putamen was positively correlated with levodopa equivalent daily dose (LEDD), Hoehn & Yahr (HY) stage and disease duration. The PostC/SMG in PD was negatively correlated with the Unified Parkinson’s Disease Rating Scale (UPDRS-III) score. Our results suggest that PD is related to widespread abnormal brain activities, and the abnormalities of ALFF in PD are associated with specific frequency bands. Future studies should take frequency band effects into account when examining spontaneous neural activity in PD.